1988
DOI: 10.1210/jcem-67-5-1068
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Interrelationships Between the Circadian Rhythms of Serum Parathyroid Hormone and Calcium Concentrations*

Abstract: The temporal relationships between the circadian rhythms of serum PTH, total calcium (Cat), and phosphate (Pi) and plasma ionized calcium (Cai) concentrations were determined in 9 normal men. Blood samples were collected every half hour for 24 h. Serum PTH was measured by an RIA specific for the midregion of the molecule. The mean circadian pattern for each variable was derived by calculating the average value across all men at concurrent time points. After the data were smoothed by the method of running means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 26 publications
7
44
4
Order By: Relevance
“…This temporal sequence does not support the concept that the circadian variations in We found a diurnal pattern of plasma total and albumin-adjusted calcium similar to that reported in previous studies with low levels during the night, a peak in the forenoon and high levels during the day (19,20,24). Our finding that plasma calcium and PTH levels correlated negatively is in agreement with most previous studies (24). Food intake is known to be a major determinant of renal calcium excretion, as a rapid rise in calcium excretion occurs after a meal (6,22).…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…This temporal sequence does not support the concept that the circadian variations in We found a diurnal pattern of plasma total and albumin-adjusted calcium similar to that reported in previous studies with low levels during the night, a peak in the forenoon and high levels during the day (19,20,24). Our finding that plasma calcium and PTH levels correlated negatively is in agreement with most previous studies (24). Food intake is known to be a major determinant of renal calcium excretion, as a rapid rise in calcium excretion occurs after a meal (6,22).…”
Section: Resultscontrasting
confidence: 80%
“…However, in our study, total plasma 1,25(OH) 2 D as well as the free 1,25(OH) 2 D index showed a nadir in the morning with an increase in the day time during which regular meals were served. This temporal sequence does not support the concept that the circadian variations in We found a diurnal pattern of plasma total and albumin-adjusted calcium similar to that reported in previous studies with low levels during the night, a peak in the forenoon and high levels during the day (19,20,24). Our finding that plasma calcium and PTH levels correlated negatively is in agreement with most previous studies (24).…”
Section: Resultssupporting
confidence: 61%
“…The origin of the circadian rhythm for PTH, however, is not clear. It is not driven by changes in serum ionized Ca 2þ concentration which exhibits one or more troughs during the afternoon but is largely stable between midnight and 06:00 h (Calvo et al, 1991;Markowitz et al, 1988). Nevertheless, the diet exerts a considerable influence because the circadian rhythm for PTH is abolished by fasting over several days (Fraser et al, 1994).…”
Section: Is the Car A Target For The Toxicity Of Aromatic L-amino Acimentioning
confidence: 99%
“…Logue et al [81] recommend that blood samples should be collected between 10:00 and 16:00 and results interpreted against a reference range based on this [65] 12.00-20.00 -20.00 08.00 Calvo et al [67] 02.00-04.00 18.00-20.00 18.00 and 02.00 10.00 and 20.00 Chapotot et al [68] 23.00-07.00 15.00-23.00 --El-Hajj et al [69] 01.00-03.00 17.30 03.14 10.00-11.00 Fraser et al [71] 22.00-07.00 14.00-22.00 06.12 09.30-10.30 Generali et al [72] --17.15 -Greenspan et al [74] 03.20 15.20 -12.00 Greenspan et al [75] 23.35 ± 05.25 , 20.30 ± 02.10 ---Herfarth et al [76] No night samples P.M. 14.00 09.30 Joseph et al [77] 22.00-24.00 , 24.00-02.00 14.00-17.00 09.46-13.15 , 10.45-13.25 -Jubiz et al [78] 02.00-04.00 --08.00 Kitamura et al [79] A.M. -23.00 ± 4 -Logue et al [82] 02.00-06.00 -04.05 10.00 Logue et al [81] A.M. -04.05 09.30 Markowitz et al [83] 04.00 20.00 --Nielsen et al [84] P.M. sampling time. Since the data were derived using first or second generation assays, it is possible that the reported diurnal variation of PTH could reflect differential clearance of PTH fragments over a 24 h period, e.g., with reduced renal clearance of (7-84) PTH at night reflecting decreased glomerular filtration rate at night [92].…”
Section: Circadian Variationmentioning
confidence: 99%